The prevalence of stigma and self-blame and their associations with psychosocial well-being among Vietnamese advanced cancer patients: An approach study - Tuong, Phan Nguyen; Lee, Audrey Jia Jia; Hiep, Pham Nhu; Quyen, Phan Thi Do; Khoa, Tran; Bao, Dang Hoai; Teo, Irene; Malhotra, Chetna; Finkelstein, Eric A; Ozdemir, Semra (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Purpose: This study aimed to (1) assess perceived stigma, behavioural self-blame (BSB) and characterological self-blame (CSB) among Vietnamese advanced cancer patients, and (2) to investigate the associations between perceived stigma and psychosocial well-being, and between self-blame (behavioural and characterological) and psychosocial well-being. Methods: This study involved 200 Vietnamese stage-4 solid cancer patients. Psychosocial well-being was measured using Center for Epidemiologic Studies Depression Scale (CES-D), and the social wellbeing (SWB) and emotional well-being (EWB) domains of the Functional Assessment of Cancer Therapy-General. Perceived stigma was assessed using sense of stigma subscale from Kissane’s Shame and Stigma Scale. BSB and CSB were identified when patients reported their behaviour or character as the reason for their cancers. Multivariable linear or logistic regressions were used to investigate the associations while controlling for patient characteristics. Results: A large proportion of patients reported perceived stigma [%, 95% Confidence Interval(CI)=79.0% (72.7%,84.1%)], BSB [%(CI)=56.3% (49.3%,63.1%)] or CSB [%(CI)=62.3% (36.9%,50.7%)]. Patients who perceived stigma reported lower EWB [ß(CI)=-0.3 (-0.4,-0.1); p=0.004) and greater depressive symptoms [ß(CI)=0.6 (0.3,0.9); p=0.000). BSB was not significantly associated with poorer psychosocial outcomes while patients with CSB reported lower EWB [ß(CI)=-1.8 (-3.4,-0.3); p=0.021] and greater depressive symptoms [ß(CI)=2.7 (0.1,5.4); p=0.045]. Conclusion: This study showed that most patients perceived stigma and reported BSB or CSB; and perceived stigma and CSB were associated with lower EWB and greater depressive symptoms among Vietnamese patients. Interventions should be developed to reduce perceived stigma and self-blame among this population.